Grief Psychotherapy to Improve Mental Health of Covid-19 Survivors: Experimental Study in Mataram City (Jurusan Bimbingan dan Konseling Islam, 2022)
The research that I did was a quantitative experimental study that tried to identify the effects of grief psychotherapy on Covid-19 survivors. The population used is covid19 survivors in the city of Mataram. Furthermore, the samples involved were adolescents with low mental health criteria based on the scale provided by the researcher. In this study researchers used grief psychotherapy to improve the health of covid19 survivors. In the normality test output, it can be seen that the value of Sig. (p value) from Kolmogorov Smirnov and Shapirowilk </= 0.05, which means that Ho is rejected (Ha is accepted) based on the Asymo Sign results. (2-tailed = 0.058) which means 0.058> 0.05 so that there is an effect of grief psychotherapy on mental health